JENIS DAN POPULASI SERANGGA HAMA YANG BERASOSIASI PADA TANAMAN KENTANG (Solanum tuberosum L) DI KECAMATAN MODOINDING - Audy R. Bororing; Juliet M.E. Mamahit; Daisy S. Kandowangko; Noni N. Wanta (Universitas Sam Ratulangi, 2015)
ABSTRACTThe research aims to find out about the type of insect pests population in potato plants Solamun tuberosum L. in Modoinding, South Minahasa. The research was conducted on the potato plants in Modoinding, South Minahasa. The research was carried out by using the survey method on potato in Modoinding's villages, South Minahasa, such as Palelon Village, Makaaroyen Village, and Lineleyan Village. The sampling was carried out with a diagonal incision method that established of five sub-plot that is on the corner and the middle of the sampling sites. The sampling was done by using insect nets that swung above the potato crop for ten times the double swing. The netted insects are immediately put into the